Comparison of whole body magnetic resonance imaging (WBMRI) to whole body computed tomography (WBCT) or 18F-fluorodeoxyglucose positron emission tomography/CT (18F-FDG PET/CT) in patients with myeloma: Systematic review of diagnostic performance. (April 2018) - Gariani, Joanna; Westerland, Olwen; Natas, Sarah; Verma, Hema; Cook, Gary; Goh, Vicky
Highlights: Current studies are limited by methodological heterogeneity, potential accrual bias and lack of an independent reference standard for lesions. Meta-analysis is not possible currently due to the quality of studies to date. Further prospective research is required to assess the impact on management. Abstract: Objectives: To undertake a systematic review to determine the diagnostic performance of whole body MRI (WBMRI) including diffusion weighted sequences (DWI) compared to whole body computed tomography (WBCT) or 18 F-fluorodeoxyglucose positron emission tomography/CT ( 18 F-FDG PET/CT) in patients with myeloma. Methods: Two researchers searched the primary literature independently for WBMRI studies of myeloma. Data were extracted focusing on the diagnostic ability of WBMRI versus WBCT and 18 F-FDG PET/CT. Meta-analysis was intended. Results: 6 of 2857 articles were eligible that included 147 patients, published from 2008 to 2016. Studies were heterogeneous including both newly diagnosed & relapsed patients. All were single centre studies. Four of the six studies (66.7%) accrued prospectively and 5/6 (83.3%, 3 prospective) included WBMRI and 18 F-FDG PET/CT. Three of seven (42.9%) included DWI. The lack of an independent reference standard for individual lesions was noted in 5/6 (83.3%) studies. Studies reported that WBMRI detected more lesions than 18 F-FDG PET/CT (sensitivity 68–100% versus 47–100%) but was less specific (specificity 37–83% versus 62–85.7%). No paper assessed impact on management. Conclusions: Studies were heterogeneous, the majority lacking an independent reference standard. Future prospective trials should address these limitations and assess the impact of WBMRI on management.